Literature Review: Environmental Risk Factors of Leptospirosis in Indonesia - Ike Rachmawati; Mateus Sakundarno Adi; Nurjazuli Nurjazuli (Poltekkes Kemenkes Palu, 2023)
Leptospirosis is a zoonotic disease which becomes a health problem in several regions in Indonesia. In 2020, there were 1,170 cases of Leptospirosis with a CFR of 9.1% spread across 8 Provinces. This study aims to determine the environmental factors that influence the incidence of leptospirosis in Indonesia. The method applied here was literature review through the Google Scholar, Pubmed and GARUDA databases which examined the environmental factors of leptospirosis in Indonesia. This was a case control study with cross sectional design with a range of published journal publications from 2016–2022. The number of samples in this study were 11 articles. The results of the study indicated that there were several environmental risk factors for the incidence of leptospirosis in Indonesia, namely the presence of standing water around the house, the poor maintained condition of ditches, the existence of trash bins that did not meet the requirements, the distance between the house and the open drain and the presence of rats inside and outside the house, and 7 articles found the presence of rats as the most dominant influential factor. Communities in leptospirosis endemic areas are expected to be more concerned with the condition of the surrounding environment and always maintain the cleanliness of their houses to prevent rats breeding as a medium for the spread of leptospirosis.